2016
DOI: 10.1093/pm/pnw274
|View full text |Cite|
|
Sign up to set email alerts
|

Patients with Concomitant Chronic Neck Pain and Myofascial Pain in Masticatory Muscles Have More Widespread Pain and Distal Hyperalgesia than Patients with Only Chronic Neck Pain

Abstract: TMD + CNP participants had more areas of pain and also showed widespread pain hyperalgesia. Both groups of participants had psychological factors positively associated with STAI and WP; further, PCS and the PPT at the extratrigeminal region were negatively associated with each other in both groups, except for the left tibialis in the TMD + CNP group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
1
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 72 publications
6
39
1
3
Order By: Relevance
“…a chemokine implicated in pain induction; Saika, Kiguchi, Kobayashi, Fukazawa, & Kishioka, 2012), consistent with data in LBP indicating higher CRP and IL‐6 to be associated with higher pain intensity (Klyne et al., 2017). In neck pain, widespread hyperalgesia has been widely reported, primarily in WAD (Stone, Vicenzino, Lim, & Sterling, 2013) but also in NTNP (Lopez‐de‐Uralde‐Villanueva, Beltran‐Alacreu, Fernandez‐Carnero, Kindelan‐Calvo, & La Touche, 2016; Munoz‐Garcia, Lopez‐de‐Uralde‐Villanueva, Beltran‐Alacreu, La Touche, & Fernandez‐Carnero, 2017). This hyperalgesia has been attributed to central sensitization due to its widespread distribution at both local (neck) and distal (upper and lower limbs) sites, and sensitivity to a range of noxious stimuli (thermal, mechanical and electrical) (Curatolo et al., 2001; Stone et al., 2013; Van Oosterwijck et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…a chemokine implicated in pain induction; Saika, Kiguchi, Kobayashi, Fukazawa, & Kishioka, 2012), consistent with data in LBP indicating higher CRP and IL‐6 to be associated with higher pain intensity (Klyne et al., 2017). In neck pain, widespread hyperalgesia has been widely reported, primarily in WAD (Stone, Vicenzino, Lim, & Sterling, 2013) but also in NTNP (Lopez‐de‐Uralde‐Villanueva, Beltran‐Alacreu, Fernandez‐Carnero, Kindelan‐Calvo, & La Touche, 2016; Munoz‐Garcia, Lopez‐de‐Uralde‐Villanueva, Beltran‐Alacreu, La Touche, & Fernandez‐Carnero, 2017). This hyperalgesia has been attributed to central sensitization due to its widespread distribution at both local (neck) and distal (upper and lower limbs) sites, and sensitivity to a range of noxious stimuli (thermal, mechanical and electrical) (Curatolo et al., 2001; Stone et al., 2013; Van Oosterwijck et al., 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, alterations of pain processing have been investigated in patients with neck pain, showing local and distant mechanical hyperalgesia [18]. Regarding nociceptive processing alterations, other researchers have found that some subgroups of patients with chronic neck pain present generalized and bilateral hyperalgesia in addition to local hyperalgesia in the cervical region, as well as functional alterations such as decreased range of cervical movement [19][20][21]. Even in some subgroups, we have found that generalized pain is associated with psychosocial factors such as anxiety [20].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the management of neck pain and its related alterations, attentional distraction-defined as shifting the attention away from the pain-is a commonly used strategy. In this context, virtual reality (VR) is defined as a computing system used to create an artificial world in which users have the impression of being able to navigate and manipulate objects in it [19,20]. VR treatment is based on three basic elements: simulation, interaction and immersion.…”
Section: Introductionmentioning
confidence: 99%
“…Although previous research on pain expansion had also found statistically significant differences in terms of the age variable, the difference was not considered clinically relevant (Muñoz-García et al, 2016).…”
Section: Study Limitationsmentioning
confidence: 82%